Dental anxiety – conditions, models, therapy - Małgorzata Sobol-Kwapińska; Alicja Senejko; Leszek Jaśkiewicz; Anna Kwiatkowska (Journal of Medical Science, 2018)
Dental anxiety is a condition suffered by many dental patients. It causes psychological discomfort and avoidance of dental appointments, which in turn may lead to oral health issues. Dental anxiety has not yet been fully explored and seems to be still posing challenge to both dentists and psychologists. The aim of this article is to review dental anxiety studies, paying particular attention to the conditions, social, demographic and psychological correlations, as well as the ramifications of this type of anxiety. The article presents the most common psychological models of dental anxiety, methods to measure this type of anxiety and therapy techniques used with patients suffering from dental anxiety.